2017
DOI: 10.14260/jemds/2017/351
|View full text |Cite
|
Sign up to set email alerts
|

Role of Placental Localisation in Prediction of Pregnancy Induced Hypertension

Abstract: BACKGROUNDPregnancy-induced hypertension is one of the leading causes of foetal and maternal morbidity and mortality worldwide. In our country, the prevalence of the disease is 5-15% and perinatal death rate due to PIH is 20%. Early detection becomes very essential as the disease is detected in advanced stages most of the times. Hence, screening for the prediction of PIH becomes necessary for improving maternal and foetal outcome. Aims-To evaluate the relationship between placental location and occurrence of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…In women with preeclampsia, 33 (70.21%) were primigravidae, and in normotensive women, 47 (56.63%) were primigravidae. The study by Nanthini et al [ 15 ] and Naik et al [ 10 ] was comparable to our study. In the Kaku et al [ 12 ] study, preeclampsia appeared 30-34 weeks earlier than ours.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In women with preeclampsia, 33 (70.21%) were primigravidae, and in normotensive women, 47 (56.63%) were primigravidae. The study by Nanthini et al [ 15 ] and Naik et al [ 10 ] was comparable to our study. In the Kaku et al [ 12 ] study, preeclampsia appeared 30-34 weeks earlier than ours.…”
Section: Discussionsupporting
confidence: 92%
“…In women with preeclampsia, among 47 women, 32 (68.09%) were diagnosed with preeclampsia between 36-39 weeks of pregnancy. In the study by Nanthini et al [ 15 ], 64.3% were diagnosed with preeclampsia between 36 and 40 weeks, and in Naik et al [ 10 ], 52.3% of the cases developed preeclampsia between 37 and 40 weeks, which was comparable to our study, but Kaku et al [ 12 ] found that preeclampsia was seen in 30-34 weeks, which was found to be earlier than the findings of our study. In this study, among 47 women with preeclampsia, only 44 or 95.7% of women without preeclampsia and only 4.26% with severe preeclampsia, which was comparable to Nanthini et al [ 15 ] and Naik et al [ 10 ] (15.26%) higher incidence of women with severe preeclampsia than our study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation